Feasibility Study dan Detail Engineering Design Pembangkit Listrik Tenaga Surya (PLTS) komunal di Universitas Teknologi Sumbawa - Aryanto, Nova; Jaya, Ahmad; Darmawan, Indra (DIELEKTRIKA, 2022)
Sumbawa University of Technology (UTS) is an educational institution whose territory has the potential to establish a Solar Power Plant (PLTS), which has an average air temperature of 25oC. This temperature allows the solar module to work to convert solar energy into electrical energy. In this study using primary and secondary data on the UTS load profile, to design the PV mini-grid construction by conducting a feasibility study and calculating the detailed Engineering Design (DED) which includes the calculation of generating capacity, the number of solar modules, batteries, Solar Charge Controller (SCC). ), and the required Inverter. The results of this study indicate that the generating capacity needed by UTS is 1,542 MWp to supply 14 buildings with a daily electricity requirement of 513 kWh where this need is utilized during activity hours (at 07.30 to 17.00 WITA), then 1450 solar modules are needed with power output of 200 Wp, 189 Batteries with a battery capacity of 12 Volt 1000 Ah/unit, 8 SCCs with a Maximum Power Point Tracking (MPPT) interval of 64 -128 Volts, and 62 inverters with a capacity of 5000 wat/unit and Output voltage (Vac) of 240 Volt